KUBY. Inmunología - Punt, Jenni; Stranford, Sharon A.; Jones, Patricia P.; Owen, Judith A. (McGraw-Hill's AccessMedicina., 2020)
Like all previous authors of this book, we focus on the idea that immunology is best taught and learned experimentally, and we have maintained that emphasis in this edition. Our goal is for students to complete an immunology course, not only with a firm understanding of the content, but also with a clear sense of how key discoveries were made, what interesting questions remain, and how they can best be answered. We believe this approach ensures that students master fundamental immunological concepts, internalize a view of immunology as an active and ongoing process, and develop the ability to contribute new knowledge themselves.